- Thread starter
- Admin
- #1

- Feb 14, 2012

- 3,937

$p+8q+27r+64s=1$

$8p+27q+64r+125s=27$

$27p+64q+125r+216s=125$

$64p+125q+216r+343s=343$

Evaluate $p+q+r+s$ and $64p+27q+8r+s$.

- Thread starter anemone
- Start date

- Thread starter
- Admin
- #1

- Feb 14, 2012

- 3,937

$p+8q+27r+64s=1$

$8p+27q+64r+125s=27$

$27p+64q+125r+216s=125$

$64p+125q+216r+343s=343$

Evaluate $p+q+r+s$ and $64p+27q+8r+s$.

- Moderator
- #2

- Feb 7, 2012

- 2,800

Compare the coefficients of $n^3$ in (*) and (**) to get $p+q+r+s = 8$.

Then put $n=-4$ in (*) and (**) to get $(-4)^3p + (-3)^3q + (-2)^3r + (-1)^3s = (-9)^3$, or $64p+27q+8r+s = 729.$

- Admin
- #3

Multiply the first equation by -1, the second by 3 the third by -3 and the system becomes:

\(\displaystyle -p-8q-27r-64s=-1\)

\(\displaystyle 24p+81q+192r+375s=81\)

\(\displaystyle -81p-192q-375r-648s=-375\)

\(\displaystyle 64p+125q+216r+343s=343\)

Adding we get:

\(\displaystyle 6p+6q+6r+6s=48\)

Hence:

\(\displaystyle p+q+r+s=8\)

b) Evaluate \(\displaystyle 64p+27q+8r+s\)

Multiply the first equation by -56, the second by 140 the third by -120 and the fourth by 35 and the system becomes:

\(\displaystyle -56p-448q-1512r-3584s=-56\)

\(\displaystyle 1120p+3780q+8960r+17500s=3780\)

\(\displaystyle -3240p-7680q-15000r-25920s=-15000\)

\(\displaystyle 2240p+4375q+7560r+12005s=12005\)

Adding, we get:

\(\displaystyle 64p+27q+8r+s=729\)

I simply solved another 4X4 system (using a CAS) to determine the values by which to multiply the given equations.

- Thread starter
- Admin
- #4

- Feb 14, 2012

- 3,937

Compare the coefficients of $n^3$ in (*) and (**) to get $p+q+r+s = 8$.

Then put $n=-4$ in (*) and (**) to get $(-4)^3p + (-3)^3q + (-2)^3r + (-1)^3s = (-9)^3$, or $64p+27q+8r+s = 729.$

Thank you for participating to both of you! Both are genius and perfect solutions to me, honestly speaking, albeit

Multiply the first equation by -1, the second by 3 the third by -3 and the system becomes:

\(\displaystyle -p-8q-27r-64s=-1\)

\(\displaystyle 24p+81q+192r+375s=81\)

\(\displaystyle -81p-192q-375r-648s=-375\)

\(\displaystyle 64p+125q+216r+343s=343\)

Adding we get:

\(\displaystyle 6p+6q+6r+6s=48\)

Hence:

\(\displaystyle p+q+r+s=8\)

b) Evaluate \(\displaystyle 64p+27q+8r+s\)

Multiply the first equation by -56, the second by 140 the third by -120 and the fourth by 35 and the system becomes:

\(\displaystyle -56p-448q-1512r-3584s=-56\)

\(\displaystyle 1120p+3780q+8960r+17500s=3780\)

\(\displaystyle -3240p-7680q-15000r-25920s=-15000\)

\(\displaystyle 2240p+4375q+7560r+12005s=12005\)

Adding, we get:

\(\displaystyle 64p+27q+8r+s=729\)

I simply solved another 4X4 system (using a CAS) to determine the values by which to multiply the given equations.Opalg's solution is much more elegant.

@Opalg, I really like your method, in fact, I like all of your posts so very much!

- Admin
- #5

- Thread starter
- Admin
- #6

- Feb 14, 2012

- 3,937

- Nov 29, 2013

- 172

Hello.

$p+8q+27r+64s=1$

$8p+27q+64r+125s=27$

$27p+64q+125r+216s=125$

$64p+125q+216r+343s=343$

Evaluate $p+q+r+s$ and $64p+27q+8r+s$.

I, as always, the more gross.

I follow the succession :

[tex]4^3p+5^3q+6^3r+7^3s=7^3[/tex]

[tex]3^3p+4^3q+5^3r+6^3s=5^3[/tex]

[tex]2^3p+3^3q+4^3r+5^3s=3^3[/tex]

[tex]1^3p+2^3q+3^3r+4^3s=1^3[/tex]

[tex]0^3p+1^3q+2^3r+3^3s=-1^3[/tex]. (a)

[tex]-1^3p+0^3q+1^3r+2^3s=-3^3[/tex]. (b)

[tex]-2^3p-1^3q+0^3r+1^3s=-5^3[/tex]. (c)

[tex]-3^3p-2^3q-1^3r+0^3s=-7^3[/tex]. (d)

[tex]-4^3p-3^3q-2^3r-1^3s=-9^3[/tex]

Therefore:

[tex]4^3p+3^3q+2^3r+1^3s=+9^3=729[/tex]

Now:

[tex](a)-(d)=27p+9q+9r+27s=342 \rightarrow{}3p+q+r+3s=38[/tex]. (e)

[tex](b)-(c)=7p+q+r+7s=98[/tex]. (f)

[tex](f)-(e)=4p+4s=60 \rightarrow{}p+s=15[/tex]. (g)

For (e):

[tex]3p+q+r+3s=38[/tex]

[tex]45+q+r=38 \rightarrow{}q+r=-7[/tex]

Therefore:

[tex]p+s+q+r=15-7=8[/tex]

Regards.

- Thread starter
- Admin
- #8

- Feb 14, 2012

- 3,937

HeyHello.

I, as always, the more gross.

I follow the succession :

[tex]4^3p+5^3q+6^3r+7^3s=7^3[/tex]

[tex]3^3p+4^3q+5^3r+6^3s=5^3[/tex]

[tex]2^3p+3^3q+4^3r+5^3s=3^3[/tex]

[tex]1^3p+2^3q+3^3r+4^3s=1^3[/tex]

[tex]0^3p+1^3q+2^3r+3^3s=-1^3[/tex]. (a)

[tex]-1^3p+0^3q+1^3r+2^3s=-3^3[/tex]. (b)

[tex]-2^3p-1^3q+0^3r+1^3s=-5^3[/tex]. (c)

[tex]-3^3p-2^3q-1^3r+0^3s=-7^3[/tex]. (d)

[tex]-4^3p-3^3q-2^3r-1^3s=-9^3[/tex]

Therefore:

[tex]4^3p+3^3q+2^3r+1^3s=+9^3=729[/tex]

Now:

[tex](a)-(d)=27p+9q+9r+27s=342 \rightarrow{}3p+q+r+3s=38[/tex]. (e)

[tex](b)-(c)=7p+q+r+7s=98[/tex]. (f)

[tex](f)-(e)=4p+4s=60 \rightarrow{}p+s=15[/tex]. (g)

For (e):

[tex]3p+q+r+3s=38[/tex]

[tex]45+q+r=38 \rightarrow{}q+r=-7[/tex]

Therefore:

[tex]p+s+q+r=15-7=8[/tex]

Regards.